2017
DOI: 10.1021/acsenergylett.7b00621
|View full text |Cite
|
Sign up to set email alerts
|

Copper Nanoparticles Installed in Metal–Organic Framework Thin Films are Electrocatalytically Competent for CO2 Reduction

Abstract: Copper nanoparticles are embedded into a solvothermally grown thin film of a zirconium metal− organic framework (MOF), NU-1000, by installing singlesite Cu(II) into the NU-1000 thin film via solvothermal deposition in MOFs (SIM) followed by electrochemical reduction of Cu(II) to metallic Cu. The obtained Cu nanoparticles are electrochemically addressable and exhibit promising electrocatalytic activity for CO 2 reduction in an aqueous electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(133 citation statements)
references
References 72 publications
4
128
0
1
Order By: Relevance
“…Another strategy to develop MOF hybrids for electrochemical CO 2 reduction was reported by Kung et al They developed as trategy to embed Cu nanoparticles into aZ r-based MOF, NU-1000,b yi nstalling the single Cu II sites into the NU-1000 thin film through solvothermald eposition in MOF structure (SIM) and the electrochemical reduction process (Figure 7a,b). [31] The production rates and Faradaic efficiencies are shown in Figure 7c [32] The FEs of CH 4 using this strategy are 2-3-fold higher than that of GDE withoutC uM OF at À2.3 Vt oÀ2.5 Vv ersus SCE. Additionally,t he Faradaic efficiency of H 2 reduced to 30 % throught he combinationo ft he Cu MOF andt he GDE.…”
Section: Mof-based Hybrid Catalystsmentioning
confidence: 94%
See 1 more Smart Citation
“…Another strategy to develop MOF hybrids for electrochemical CO 2 reduction was reported by Kung et al They developed as trategy to embed Cu nanoparticles into aZ r-based MOF, NU-1000,b yi nstalling the single Cu II sites into the NU-1000 thin film through solvothermald eposition in MOF structure (SIM) and the electrochemical reduction process (Figure 7a,b). [31] The production rates and Faradaic efficiencies are shown in Figure 7c [32] The FEs of CH 4 using this strategy are 2-3-fold higher than that of GDE withoutC uM OF at À2.3 Vt oÀ2.5 Vv ersus SCE. Additionally,t he Faradaic efficiency of H 2 reduced to 30 % throught he combinationo ft he Cu MOF andt he GDE.…”
Section: Mof-based Hybrid Catalystsmentioning
confidence: 94%
“…Reproduced with permission from reference[31].Copyright 2017 American Chemical Society. b) Energy dispersive spectroscopy( EDS) line scan and the corresponding SEM images of the Cu-SIM NU-1000t hin film.…”
mentioning
confidence: 99%
“…Furthermore, metal–organic frameworks (MOFs), which are porous crystalline materials with a 3D framework of metal ions or clusters connected by stiff bi‐ or multipodal organic linkers, are also recognized as important supporting materials. [ 121 ] Tan et al reported a Cu 2 O@Cu‐MOF restructured catalyst with a unique CO 2 ‐adsorption ability and demonstrated outstanding performance with a total FE of 79.4% toward hydrocarbon products. [ 122 ] Figure 8d shows a schematic illustration of the process of Cu 2 O@Cu‐MOF catalyst synthesis.…”
Section: Surface Structure‐dependent Catalytic Activity/selectivity Omentioning
confidence: 99%
“… Electron micrographs of MOFs that have been used as catalyst supports: a) SEM and b) TEM images of Cu 2 (CuTCPP) nanosheets . c) Top‐down and d) cross‐sectional SEM images of a Cu‐SIM NU‐1000 thin film . e, f) SEM images of the MOF catalyst film before (e) and after electrolysis (f), which revealed the retention of the plate‐like morphology .…”
Section: Mof‐related Catalysts For Co2ermentioning
confidence: 99%